THE ROLE OF LANGUAGE IN IDENTITY FORMATION: A SOCIOLINGUISTIC APPROACH (Web of Teachers: Inderscience Research, 2024)
The article is devoted to the study of the role of language in the formation of individual and collective identity using a sociolinguistic approach. Language is not only a means of communication, but also an important tool through which identity is constructed. In the article, we consider various aspects, such as the influence of dialects and accents, the use of language in the context of communities and cultural groups, and the role of language in intercultural communication. We analyze how language can reflect social, cultural and political realities, shaping the idea of "I" and "We". The study also pays attention to the dynamics of changes in identity caused by globalization and migration. Based on theoretical analysis and empirical data, the article demonstrates how language serves not only to convey information but also to express identity, emphasizing the importance of a sociolinguistic approach to the study of language and its functions.